NoSQL with MongoDB in 24 hours : Sams teach yourself (supplemental video) - Dayley, Brad; Safari eBooks ([Place of publication not identified] : Sams, 2015)
"The media elements for Sams Teach Yourself NoSQL with MongoDB in 24 Hours demonstrate key points in the text."--Resource description page.
Presenter, Brad Dayley.
Title from resource description page (viewed February 23, 2015).
Keywords: MongoDB; Databases -- Technological innovations; Information storage and retrieval systems; Non-relational databases; Electronic books